Research on Gradient Temperature Rolling Process and Deformation Uniformity of 10Ni5CrMoV Heavy Plate - Wang, Weiwei; Wang, Baoshan; Zhang, Hongliang (Manufacturing Technology Journal, 2025)
In order to solve the problem of heterogeneous deformation in the rolling process of 10Ni5CrMoV heavy plate, the effects of uniform temperature rolling (UTR) and graded temperature rolling (GTR) on the microstructure and deformation uniformity of 10Ni5CrMoV steel were studied by means of numerical simulation and verification experiment, and the strengthening mechanism of high permeability rolling process on the rolling deformation of 10Ni5CrMoV heavy steel was clarified. The results show that compared with the uniform temperature rolling process(UTR), different gradient temperature rolling processes (GTR) make the deformation area gradually expand to the core, and the deformation of the core increases significantly. The reduction rate of the first pass gradient temperature rolling processes (FGTR) is about 2.3% higher than that of uniform temperature rolling, and that of continuous gradient temperature rolling (CGTR) is about 5.3% higher than that of uniform temperature rolling. At the same time, the microstructure difference of the core surface is reduced, which is conducive to improving the uniformity of microstructure and properties. At the same time, the microstructure of the core in the rolled is uniformly refined, and the effect is significant.
Keywords: 10Ni5CrMoV steel; Heterogeneous deformation; Gradient temperature rolling; Finite element analogy; Heavy plate; Uniform temperature rolling